If you mean: 34 39 24 ... then the nth term is 39-5n and so the 100th term = -461
-n2+2n+49
tn = 34 - 9n where n = 1,2,3,...
17/3
-34 would be the 15th term.
Willies
If you mean: 34 39 24 ... then the nth term is 39-5n and so the 100th term = -461
To find the nth term of a sequence, we first need to determine the pattern or rule that governs the sequence. In this case, the sequence appears to be increasing by adding consecutive odd numbers: 3, 6, 9, 12, and so on. Therefore, the nth term formula for this sequence is Tn = 3n^2 + n. So, the nth term for the sequence 4, 7, 13, 22, 34 is Tn = 3n^2 + n.
The next term is 45 because the numbers are increasing by increments of 3 5 7 9 and then 11
The nth term is 9n-2
It is T(n) = n2 + 4*n + 2.
Well, darling, the pattern here is increasing by odd numbers starting from 1. So, the nth term for this sequence would be n^2 - 2, where n represents the position of the term in the sequence. But hey, if math isn't your thing, just keep enjoying the ride with those quirky numbers!
The nth term of the sequence 3n + 4 can be calculated by substituting the value of n into the formula. For example, if n = 1, the first term would be 3(1) + 4 = 7. If n = 2, the second term would be 3(2) + 4 = 10. Therefore, the nth term of the sequence is 3n + 4.
The given sequence appears to be increasing by 10 each time. To find the nth term, we can use the formula for arithmetic sequences: nth term = first term + (n-1) * common difference. In this case, the first term is 4 and the common difference is 10. Therefore, the nth term for this sequence would be 4 + (n-1) * 10, which simplifies to 10n - 6.
To find the nth term of a sequence, we first need to determine the pattern or rule governing the sequence. In this case, the sequence appears to be increasing by 7 each time. Therefore, the nth term can be represented by the formula Tn = 6 + 7(n-1), where n is the position of the term in the sequence.
tn = n2 + 9, n = 1,2,3,...
The nth term = 9n-2